CAR T Cells: Cancer Cell Surface Receptors Are the Target for Cancer Therapy - Behrouz Shademan; Vahidreza Karamad; Alireza Nourazarian; Cigir Biray Avcı (Tabriz University of Medical Sciences, 2022)
Immunotherapy has become a prominent strategy for the treatment of cancer. A method thatimproves the immune system's ability to attack a tumor (Enhances antigen binding). Targetedkilling of malignant cells by adoptive transfer of chimeric antigen receptor (CAR) T cells is apromising immunotherapy technique in the treatment of cancers. For this purpose, the patient'simmune cells, with genetic engineering aid, are loaded with chimeric receptors that haveparticular antigen binding and activate cytotoxic T lymphocytes. That increases the effectivenessof immune cells and destroying cancer cells. This review discusses the basic structure andfunction of CAR-T cells and how antigenic targets are identified to treat different cancers andaddress the disadvantages of this treatment for cancer.